Vessel Size Imaging (VSI) by Robust Magnetic Resonance (MR) Relaxometry: MR-VSI of Solid Tumors in Correlation with Immunohistology and Intravital Microscopy - Thorsten Persigehl; Janine Ring; Tymoteusz Budny; Anke Hahnenkamp; Sandra Stoeppeler; Lawrence H. Schwartz; Hans-Ullrich Spiegel; Walter Heindel; Stefanie Remmele; Christoph Bremer (Molecular Imaging)
The aim of this study was to evaluate a robust magnetic resonance (MR) vessel size imaging (VSI) method for the noninvasive assessment of mean vessel size in solid tumors in a clinical dose range of ultrasmall superparamagnetic particles of iron oxide (USPIO). Therefore, USPIO-enhanced MR-VSI was performed on DU-4475, MDA-MB-435, and EOMA tumor–bearing mice xenografts with known differences in angiogenic activity and vessel morphology. MR results were compared to vessel sizes determined by immunohistochemistry (anti-CD31) and by intravital microscopy (IVM). MR-VSI revealed significantly different mean vessel sizes between the xenograft models at both USPIO doses (DU-4475: 20.6 ± 4.9 mm; MDA-MB-435: 37.4 ± 8.8 μm; and EOMA: 60.3 ± 9.6 μm at 80 μmol/kg; p < .05). Immunohistochemistry revealed lower values for all tumor entities, whereas the size distribution was in line with MR-measurements. IVM corroborated the MR results for DU-4475 and MDA-MB435, but showed similar vessel sizes for MDA-MB-435 and EOMA. Our MR-VSI method allowed a noninvasive estimation of the mean vessel size in mice xenograft solid tumors with variable vascularity using a clinically relevant USPIO dose range.